On the light emitting hot evolving black holes - B, Ramanuja Srinivas; P, Kalyani; U.V, Satya Seshavatharam (International Journal of Advanced Astronomy, 2014)
Along with the presently believed black holes that are expected to be formed by gravitational collapse of massive star, there may exist primordial very hot evolving black holes and their origin may be interlinked with the Planck mass. Extending this proposal, the current universe can be considered as a huge evolving black hole of radius equal to the current Hubble length and temperature equal to 2.725 K. It can be suggested that 1) Vacuum is a great reservoir for matter and energy. 2) Planck mass can be considered as the primordial very hot baby black hole and can be called as the baby Planckion. 3) Baby Planckion will grow by absorbing the vacuum energy and thereby its geometric horizon also increases. As the baby Planckion is growing, its temperature and the tendency of vacuum energy absorption will decrease. 4) Very high temperature of the baby Planckion is the heat source for the evolving Planckion’s decreasing temperature. 5) Growing Planckion can be considered as the seed and center of any galaxy. 6) Growing Planckion will permit the emission of radiation. 6) Current universe can be considered as a huge evolving Planckion with temperature 2.725 K. In support this proposal, it is possible to guess that, in the past decreasing comic black whole temperature forced hydrogen atom to emit increased quantum of energy resulting in the observed redshift. Keywords: Planck Scale, Planck ion, Evolving Black Holes, Black Hole Temperature, Emission of a Black Hole. CMBR Temperature, Evolving Black Hole Universe.